Using microsoft office 2000 - Bott, Ed; Leonhard, Woody (New Delhi : Prentice-Hall of India, 1999)
Computer science
Keywords: Microsoft office; Programming; Web; Word; Excel; E-mail management; Powerpoint; Access; Frontpage; Visual basic